Effect of Stocking Density on the Performance of Growing Pigs - Leena K (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 1992)
The objectives of the study were, to find out the minimum floor space requirement without affecting performance in growing pigs, to assess change in the pattern of behaviour in pigs due to change in stocking rates and to find out whether there is any effect of reduction in floor space upon the growth and carcass quality of pigs. Twenty seven large White Yorkshire weanling female pigs having an average body weight of 8.5 kg and 56 days of age were assigned at random to three treatment groups. In the first (control) group of six pigs, each received lm2 of floor space (as per ISI specification) while in the second group there were nine pigs and in the third group 12 pigs received 0.75 m2 and 0.5m2 of floor space per pig respectively. Animals were provided with concentrate and allowed to consume as much as they could within a period of one hour. Total weight gain of 58.5 kg, 56.22 kg and 55.46 kg were noticed in control group, group two and group three respectively. Variations of average fortnightly body weight of pigs due to stocking density were not found to be significant. Similar trend were noticed in the case of height, length and girth. When the feed conversion efficiency was taken as whole, it was found to be highest in group III (3.746 + 0.667) and lowest in group I (3.960 + 0.864). The animals of group II were showing feed conversion efficiency between group I and group III (3.798 + 0.744). Aggressive behaviour was measured by counting the number of threats and number of ear – biting incidence. These parameters were found to be highest at higher stocking densities. When the dressing percentage with head is taken and compared to per unit weight, no apparent difference was observed between the groups (1.096; 1.360 and 1.118 per cent respectively for group I, II and III). Similar was the trend in half carcass weight, weight of the ham, carcass length and eye muscle area. The back fat thickness was found to be similar in group I and III (2.41 cm and 2.388 cm respectively) and less in group II (1.499 cm). From the experimental result to significant difference could be observed in the performance of those pigs having a floor space as per ISI specification and the one where the floor space reduced to the extent of 50 percentage.